Retrospective study on maternal outcome in referred obstetric patients in government Doon medical college - Chauhan, Monica; ., Roopal; Kochhar, Neetu (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2022)
Background: The referral system forms an integral component of any health care system, for providing essential obstetric care to women during pregnancy and childbirth. The study was conducted with an objective to identify the pattern of obstetric referrals to Doon female hospital, government Doon medical college, primary reason for referral, delay in referral, clinical course, mode of management and outcome. Methods: It is a retrospective observational study. All the referred obstetric cases were analyzed for the cause of referral, place of referral and outcome for the period of 6 months from October 2021 to march 2022. Results: In our study we found total 486 obstetric patients were referred. Maximum referred patients were in the age group of 20-30 years and 61% referrals were from Dehradun district 12.96% of cases were delayed referrals. Conclusions: Our study revealed that illiteracy and ignorance is the major factor that contributes to poor pregnancy outcome. Need of the hour is to train health care workers at primary and secondary health care center in essential and emergency obstetric care so as to avoid unnecessary referrals and reduce burden on tertiary health care hospitals and decrease in the frequency of delayed referrals so as to improve the maternal and fetal outcome.